Multicenter Prospective Comparative Study between Upper Mini-Sternotomy, and Right Anterior Mini-Thoracotomy for Isolated Aortic Valve Replacement - Yasser Mubarak; abdulaziz aljuhayim; Moath Hesham Al Ahmed; Ahmed M. Shabaan (Journal of Cardio-Thoracic Medicine)
Background: Surgical Aortic valve replacement (sAVR) is one of the most common valve surgery associated with excellent Results. SAVR can be performed via a full sternotomy (FS) or a minimal invasive surgical (MIS) approach. Many studies compared outcomes of AVR through upper mini-sternotomy (UMS) versus full sternotomy (FS) and others compared right anterior mini-thoracotomy (RAMT) versus full sternotomy (FS). Our aim was to compare early outcomes of AVR by UMS versus RAMT.Materials and Methods: The prospective, randomized, comparative multicenter study compared surgical and early outcomes of patients who underwent elective isolated SAVR from January 2021 to January 2024. All consecutive patients had aging group 65-75 years old. Patients are divided into two groups; group [RAMT] and group [UMS]. Selection of RAMT groups according to preoperative chest computed tomography (CT). All patients who had severe aortic stenosis [AS] received a bioprosthetic valve suture bioprosthetic, group [S], or sutureless (Perceval) [SURD].Results: No differences in both groups about age, preoperative risk factors, and postoperative complications. Operative time was significantly shorter for the SURD group, regardless of approach. However, nowadays a core- knot in the suture valve made almost no time difference. UMS group had less postoperative pain than RAMT group, however with using analgesic and pain killer made differences not obvious. RAMT group had more lung atelectasis, pleural effusion, and limited mobility of the right arm in the first few postoperative days. UMS group could be easily converted to FS if needed. The RAMT had more cosmetic and patient satisfaction.Conclusions: Both approaches are nearly similar in early outcomes and consider the future of total endoscopic and robotic cardiac surgery.